Retooling gender? a constructivist analysis of Tomboy Tools / by Rebecca Collins-Nelsen. - Collins-Nelsen, Rebecca (My University, 2010)
"In this study, I will examine the case of 'Tomboy Tools' as a form of gendered material culture. I will analyze the way this company has come to cross the traditional gender boundaries placed on women that has historically alienated them from the domain of tools and home repair. In attempting to bridge the historically opposing worlds of femininity and home repair, the company has used the strategy of making the tools conform to a traditionally feminine gender script (light, cute, pink, etc). Drawing on data from a content analysis, participant observation, and interviews I use a constructivist grounded theory approach (Charmaz 2006; Clarke 2005) to analyze how the identities, practices, and norms of potential female users are projected and reinforced in the design and marketing of the tools. I also consider how potential female buyers respond to these implicit assumptions, and interpret and give meanings to these new cultural artefacts and messages in often competing and contradictory ways."--Abstract
Keywords: Sex role; Home repair; Tomboy Tools Inc.; Tools - Marketing